Epigenome Editing of Potato by Grafting Using Transgenic Tobacco as siRNA Donor - Kasai, Atsushi; Bai, Songling; Hojo, Hatsune; Harada, Takeo (PLOS ONE, 2016)
In plants, it is possible to induce heritable transcriptional gene silencing (TGS) via RNA-directed DNA methylation (RdDM) using artificially synthesized small RNA (siRNA) homologous to the 5'-flanking region of the target gene. As the siRNA signal with a specific RNA determinant moves through plasmodesmata and sieve elements, we attempted to induce TGS of a transgene and an endogenous gene of potato (Solanum tuberosum) rootstock by grafting using siRNA produced in a tobacco (Nicotiana benthamiana) scion. Our results provide evidence that this system can induce TGS of target genes in tubers formed on potato rootstock. The TGS is maintained in the progeny tubers lacking the transported siRNAs. Our findings reveal that epigenome editing using mobile RNA has the potential to allow breeding of artificial sport cultivars in vegetative propagation crops.